A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank - de Carvalho, Claudio J. B.; Haseyama, Kirstern Lica F. (Zootaxa, 2018)
After a 20 years hiatus, we describe a new species, Polietina ponti sp. nov., from Madre de Dios, Tambopata River, Peru. Additionally, we propose Polietina nigra Couri & Carvalho, 1996 as a junior synonym of Polietina prima (Couri & Medeiros, 1990). A previous phylogenetic hypothesis was updated with the inclusion of the new taxon described here, which yielded a single most parsimonious tree that is similar to a previously published hypothesis (Pyrellina marsya (Pyrellina distincta (Deltotus facetus ((Polietina steini (Polietina ponti sp. nov., P. prima (P. bicolor, P. minor, P. univittata)(P. flavithorax, P. major)))(P. flavidicincta (P. rubella (P. concinna (P. orbitalis, P. wulpi)))))))). The identity of Polietina vouchers with nucleotide sequences registered in the GenBank were also verified and corrected.